Effects of nociceptin and endomorphin 1 on the electrically stimulated human vas deferens - Bigoni, Raffaella (Blackwell Science Inc, 2001)
AIMS: To examine the effects of nociceptin (NC) and endomorphin 1 (EM1) on electrical field stimulation (EFS)-induced contractions of the human vas deferens (hVD). METHODS: Concentration-response curves to NC and EM1 were constructed in the absence and in presence of peptidase inhibitors (PI). In some experiments a NC receptor antagonist, [Phe(1)ψ(CH(2)-NH)Gly(2)]NC(1–13)NH(2) [F/G], 10 µm) or naloxone (1 µm) were included. RESULTS: All data are mean(95%CI). In the presence of PI, NC inhibited twitches (E(max) = 67(44,90)%; pEC(50) = 7.28(6.95,7.61)). NC inhibition was sensitive to [F/G]. EM1 also inhibited twitches both in the absence (E(max) = 82(73,91)% pEC(50) = 7.07(6.92,7.22)) and presence (E(max) = 83(76,90)%; pEC(50) = 7.00(6.91, 7.09)) of PI. EM1 inhibition was sensitive to naloxone. CONCLUSIONS: These data suggest that hVD express NC and opioid receptors that inhibit neurogenic contractions.